Two Woodsmen and the Forest in the Kartapis near Neisa - Sencer Şahin (Gephyra, 2007)
Two Woodsmen and the Forest in the Kartapis near NeisaIn an inscription recently found in the vicinity of the village Sütleğen and dated after the term of office of the Lykiarch Kil(l)ortes (AD 134), Artemes and Hermaios, two citizens of the city of Neisa, claim to have been the only ones to know how to move felled trees upwards and out of the wood in the Kartapis. Although not having a corresponding parallel in the geography of Lycia, the toponym Kartapis (-idos) corresponds to Lycian personal names such as Kartadis, Kartalis or Kartakes. The inscription tells us that logging in the woods of the Kartapis encountered tremendous topographical difficulties and therefore required a certain expertise on the part of the loggers. The Kartapis is certainly to be identified with the very narrow and deep canyon-type gorge of the Kıbrıs Deresi, which starts in the immediate vicinity of the site where the inscription was found. The cedar woods in this untouched and barely penetrable gorge were very probably the property of a local elite, who probably commissioned the two loggers. It could well be that it was the family of the Dionysii from which stemmed numerous Lykiarchs in the 2nd and 3rd centuries.